Zmiany strukturalne w szkolnictwie zawodowym w latach 1990-1997 - Kwiatkowski, Stefan M (Wydawnictwo Naukowe UAM w Poznaniu, 1999)
One of the most important elements of the vocational education reform is the modification of its structure from the point of view of both school numbers and enrolment. The article presents the analysis of data carried out from 1990 to 1997, On this background a structural prognosis concerning the vocational education system is presented with respect to the latest reform proposals.
Structural changes in vocational education in the period 1990-1997
Keywords: Reforma edukacji; Reform of education; Koncepcja szkoły; Conception of school; Szkolnictwo; education; Oświata; Learning